Link between sterile inflammation and cardiovascular diseases: Focus on cGAS-STING pathway in the pathogenesis and therapeutic prospect - Du, Yao; Zhang, Hui; Nie, Xiaoyan; Qi, Yajun; Shi, Shi; Han, Yingying; Zhou, Wenchen; He, Chaoyong; Wang, Lintao (Frontiers in Cardiovascular Medicine, 2022)
Sterile inflammation characterized by unresolved chronic inflammation is well established to promote the progression of multiple autoimmune diseases, metabolic disorders, neurodegenerative diseases, and cardiovascular diseases, collectively termed as sterile inflammatory diseases. In recent years, substantial evidence has revealed that the inflammatory response is closely related to cardiovascular diseases. Cyclic guanosine monophosphate–adenosine monophosphate synthase (cGAS)-stimulator of interferon genes (STING) pathway which is activated by cytoplasmic DNA promotes the activation of interferon regulatory factor 3 (IRF3) or nuclear factor-κB (NF-κB), thus leading to upregulation of the levels of inflammatory factors and interferons (IFNs). Therefore, studying the role of inflammation caused by cGAS-STING pathway in cardiovascular diseases could provide a new therapeutic target for cardiovascular diseases. This review focuses on that cGAS-STING-mediated inflammatory response in the progression of cardiovascular diseases and the prospects of cGAS or STING inhibitors for treatment of cardiovascular diseases.